Visualising early-stage liquid phase organic crystal growth via liquid cell electron microscopy. Issue 7 (11th February 2020) - Cookman, Jennifer; Hamilton, Victoria; Price, Louise S.; Hall, Simon R.; Bangert, Ursel
Abstract : Here, we show that the development of nuclei and subsequent growth of a molecular organic crystal system can be induced by electron beam irradiation by exploiting the radiation chemistry of the carrier solvent. Abstract : Here, we show that the development of nuclei and subsequent growth of a molecular organic crystal system can be induced by electron beam irradiation by exploiting the radiation chemistry of the carrier solvent. The technique of Liquid Cell Electron Microscopy was used to probe the crystal growth of flufenamic acid; a current commercialised active pharmaceutical ingredient. This work demonstrates liquid phase electron microscopy analysis as an essential tool for assessing pharmaceutical crystal growth in their native environment while giving insight into polymorph identification of nano-crystals at their very inception. Possible mechanisms of crystal nucleation due to the electron beam with a focus on radiolysis are discussed along with the innovations this technique offers to the study of pharmaceutical crystals and other low contrast materials.